What should you know about limbic encephalitis? - Machado, S (2012)
Autoimmune encephalitis is an inflammatory disorder characterized by a subacute impairment of short-term memory, psychiatric features and seizures. It is often associated with a variety of other neurological symptoms, and its differential diagnosis is wide, leading to challenges in its recognition. It used to be regarded as a rare disease, usually paraneoplastic and with poor prognosis. However, with the recent recognition of membrane-surface directed antibodies, it is now known that in a substantial proportion of cases there is no association with any malignancy and there is a good prognosis if treated. Hence, early recognition and prompt initiation of immunotherapies are of great importance.